Survival Analysis on the Risk Factors of Womens with Cervical Cancer: A Case Study at Black Lion Hospital, Addis Ababa, Ethiopia. - Dessalew Sheferaw Yesuf; Tigist Jegnaw Lakew; Kasim Mohammed Yesuf (Asian Journal of Medical Radiological Research, 2019)
Background: Cancer is a group of diseases characterized by the uncontrolled growth and spread of abnormal cells. If the spread is not controlled, it can result in death. The objective of this study was to identify factors associated with the survival time of cervical cancer patients in Black Lion Hospital Addis Ababa, Ethiopia. Subjects and Methods: A retrospective cohort study was conducted in Black Lion Hospital Addis Ababa, Ethiopia. Information on patients enrolled from December 2014 and had at least one follow-up until January 2017 time period in oncology center was used in this study. Kaplan-Meier survival curves and Log-Rank tests were used to compare the survival experience of different category of predictors. Semi-Parametric survival models were employed to examine the effect of explanatory variables on survival times.Results:A total of 518 cervical cancer patients in Black Lion Hospital were included in the study. Out of 518 cervical cancer patients, 49.04% were live in urban area and 50.96 % were live in rural area. The instantaneous risk of death for urban place of residence is 2.04 times the instantaneous risk of death for rural place of residence. The instantaneous risk of death for patients with hypertension has 2.15 greater risk of death than those patients without hypertension. Improved the survival of patients was an integral part of controlling cervical cancer.Conclusion: It has been found that 16% of the considered patients were died and the remaining 84% were censored at the end of the study. The median survival time of cervical cancer patients was 31months after diagnosis. The covariates those are more significant for cervical cancer patients are age, place of residence, hypertension, FIGO stage, histological type, and histological grade and HIV status.